Longitudinal Study of Lower Urinary Tract Function in Children with Anorectal Malformation - Borg, Helena; Holmdahl, Gundela; Doroszkievicz, Monica; Sillen, Ulla (European Journal of Pediatric Surgery, 2014)
Neurogenic bladder dysfunction (NBD) in children with anorectal malformation (ARM) has been reported in many publications, but with variations in prevalence and connection to type of ARM and spinal cord/sacral malformations. The prevalence of ARM patients with functional nonneurogenic dysfunction, on the contrary, has been addressed only sparsely. Since constipation and soiling have been shown to often accompany functional urinary tract symptoms in children without malformations, and treatment of constipation often improves bladder symptoms, it is interesting to assess such a connection in ARM patients. This study assessed lower urinary tract dysfunction (LUTD) overall in ARM children. Special attention was paid to whether patients with poor bowel function had more LUT symptoms, excluding those with urological reasons for the LUTD (NBD and urogenital malformations).Patients and Methods Children with ARM, excluding those with perineal fistula, were included (n = 41). Bladder function was investigated at 5 (n = 25), 10 (n = 28), and 15 (n = 13) years using a structured questionnaire and flow residual. A scoring system was used. In addition, healthy children of comparable age were assessed using the same questionnaire. Data on bowel function were also available, as presented in a recent article. In children with NBD, cystometry was also used at follow-up.Results NBD was seen in 9 children (22%), whereas nonneurogenic LUTD was diagnosed in 14 cases (34%). A clear difference between the groups was seen, with a permanent dysfunction in neurogenic and often transient and mild in the nonneurogenic LUTD. A significant correlation between LUTD and bowel dysfunction was identified when all LUTD was included (p = 0.045). When children with neurogenic and urological causes of LUTD were excluded, the remaining children with LUTD had lower scores for bowel function than those with normal bladder function, but the difference was not significant (p = 0.1291).Conclusion Poor bowel function was often seen together with LUTD. In children with NBD, the connection was attributable to a mutual impairment of the nerve supply to both systems. Children with nonneurogenic and nonurological causes of the LUTD also had lower bowel scores than those with normal bladder function; although not significant, it suggests that poor bowel function was responsible for an increase in LUT symptoms.
Keywords: anorectal malformation; non–neurogenic bladder dysfunction; neurogenic bladder dysfunction